THE IMPACT OF THE DMAIC MODEL IN WASTE REDUCTION: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT ZAIN IRAQ TELECOMMUNICATIONS COMPANY - Fakhri Ibadi Ali; Prof. Dr. Aseel Ali Mezher (Scholars Digest Publishing, 2025)
The current study aims to test the effect of the (DMAIC) model in reducing Waste in Zain Iraq Telecommunications Company, and to identify the reality of the company's situation, the study community, and help it solve the problems it faces and develop appropriate solutions to overcome these problems and deal with the changing environment effectively and efficiently. The study adopted the comprehensive inventory method, meaning that the study community is the same as the study sample, and on this basis, an electronic form was approved to be distributed to the target sample through agreement with the company's public relations department. Accordingly, the study sample included (282) valid answers for analysis from a community of (290). The descriptive analytical approach was relied upon in this study.
Keywords: DMAIC, Waste Reduction, Zain Iraq.